Possible Future Career Challenges and Associated Factors among Dental Students and Interns - Sarah Fita; Faris Alshuraim; Abdullah Almulhim; Jehan AlHumaid; Muhanad Alhareky; Muhammad Nazir (International Journal of Dentistry, 2020)
Background. Dental students face a variety of challenges as they enter the dental profession. The study aimed at assessing dental students’ opinions about their perceived future career challenges in the dental profession and the associated factors. Materials and Methods. This cross-sectional study of 637 students representing different public and private dental colleges was conducted in Saudi Arabia. The participants responded to a pretested questionnaire conducted online. Results. There were 59.7% (n = 380) of males and 40.3% (n = 257) of females, and the mean age of the students was 21.80 (±2.14) years. The majority of participants thought that they will have difficulties in establishing their private clinic (63.9%) and finding a government job (>60%). Senior students were more likely to perceive getting a government job (OR = 1.79, P=0.02), securing an admission into specialty program (OR = 2.75, P=0.001), and establishing a private dental clinic (OR = 2.51, P=0.001) as future career challenges than junior students. Similarly, female gender was associated with increased perception of challenges about finding a government job (OR = 1.911, P=0.002), getting an admission into specialty program (OR = 1.5, P=0.038), and establishing a private clinic (OR = 2.02, P=0.001). In addition, low academic score and low level of father’s education were associated with increased odds of perceiving challenges of finding a government job and getting an admission into specialty programs. Conclusions. Establishing a private clinic and getting a government job were the most common career challenges. Senior students, female students, and students with low academic scores had increased likelihood of facing employment and academic-related difficulties.